2016
DOI: 10.1017/s0031182016001050
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the Brazilian flathead Percophis brasiliensis reflect West Atlantic biogeographic regions

Abstract: With the aim of evaluating the utility of marine parasites as indicators of zoogeographical regions in the South West Atlantic, we analyzed data on assemblages of long-lived larval parasites of 488 specimens of Percophis brasiliensis distributed in 11 samples from nine localities covering the entire distribution of the species in the Argentine biogeographical Province. Near half a million long-lived parasite individuals belonging to 17 species present in the whole sample displayed clear latitudinal patterns. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…However, nMDS analyses showed that Z. conchifer departed from the general zoogeographical pattern displayed by the other samples, which in turn, agreed with biogeographical schemes recognized in the South-West Atlantic [ 48 ]. Indeed, the apparent separation of samples in two groups corresponding to the Bonaerensean District of the Argentine Province and to the Magellanic Province, characterized by low and high values of prevalence, respectively, confirms the value of larval Anisakis as zoogeographical indicators [ 9 , 34 ]. On the other hand, the two ecotonal hake samples between these two zoogeographical units (Mh3 and Mh4) clustered with Magellanic and Bonaerensean samples, respectively, indicating a higher influence of each mass of water on the populations of Anisakis in fish at these transitional zones.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, nMDS analyses showed that Z. conchifer departed from the general zoogeographical pattern displayed by the other samples, which in turn, agreed with biogeographical schemes recognized in the South-West Atlantic [ 48 ]. Indeed, the apparent separation of samples in two groups corresponding to the Bonaerensean District of the Argentine Province and to the Magellanic Province, characterized by low and high values of prevalence, respectively, confirms the value of larval Anisakis as zoogeographical indicators [ 9 , 34 ]. On the other hand, the two ecotonal hake samples between these two zoogeographical units (Mh3 and Mh4) clustered with Magellanic and Bonaerensean samples, respectively, indicating a higher influence of each mass of water on the populations of Anisakis in fish at these transitional zones.…”
Section: Discussionmentioning
confidence: 85%
“…Lanfranchi et al [ 29 ] included data on other host species recognized as harbouring parasite assemblages representative of neighbouring zoogeographical regions, characterized by these masses of water [ 9 , 33 , 34 ]. These waters, with subtropical and sub-Antarctic origins, affected the structure of parasite communities in the ecotone by acting as sources of infective stages of helminth species (acanthocephalans, nematodes, cestodes) typical of adjacent zoogeographical units, which were considered as reliable indicators to define such transitional regions.…”
Section: Introductionmentioning
confidence: 99%
“…The parasite fauna of P. brasiliensis is probably one of the best known in the south鈥恮estern Atlantic (Braicovich et al, 2017; Braicovich & Timi, 2008, 2010). In new samples collected 13 years after prior work, and from the southern distribution area, two new parasites were recorded, yielding a total of 38 species of parasites known for this host.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this case, changes related to short鈥恡erm or seasonal causes were avoided by restricting comparative analyses to larval parasites, all of them living in the body cavity or internal tissues. Members of this guild are persistent for long periods or even for the entire life of hosts (Braicovich et al, 2017; Lester & MacKenzie, 2009; Timi & MacKenzie, 2015), and consequently, seasonality is not expected to occur. Furthermore, both samples from ER (2005 and 2018) were caught during the same season (October), further reducing any expected influence of seasonality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation